Exploring AI Adoption Dynamics and Entrepreneurial Orientation in Czech Chemical SMEs: A Pilot Study Perspective - Hrubý, Vojtěch (University of Pardubice, 2024)
This article outlines a pilot study aimed at exploring the influence of Entrepreneurial Orientation (EO) on Artificial Intelligence (AI) adoption and firm performance within Czech chemical SMEs. With dual aims, the study first evaluates the feasibility of the main research design and secondly develops and validates an innovative instrument for measuring AI adoption. Through a quantitative survey, 107 Czech chemical SMEs were engaged, focusing on the practicality of research methodologies and the initial testing of measurement tools, especially for AI adoption. Despite a modest response rate, the study met its methodological objectives, offering insights into AI integration and EO's complexity within the sector. The initial findings hint at the need for broader engagement strategies in the subsequent study, reflecting the challenges of researching niche markets. Significantly, the creation of the AI adoption tool marks a considerable advancement, addressing a gap in existing research tools. This study not only underscores the importance of pilot testing in social sciences, especially within specialized sectors, but also its findings and methodologies serve as a blueprint for future research, emphasizing the adaptation of strategies to industry-specific and geographical peculiarities. By establishing a methodological foundation for in-depth future research, this pilot study promises enhanced understanding of EO's impact on AI adoption strategies and performance outcomes in the Czech chemical industry, directly addressing a critical research gap.

This article outlines a pilot study aimed at exploring the influence of Entrepreneurial Orientation (EO) on Artificial Intelligence (AI) adoption and firm performance within Czech chemical SMEs. With dual aims, the study first evaluates the feasibility of the main research design and secondly develops and validates an innovative instrument for measuring AI adoption. Through a quantitative survey, 107 Czech chemical SMEs were engaged, focusing on the practicality of research methodologies and the initial testing of measurement tools, especially for AI adoption. Despite a modest response rate, the study met its methodological objectives, offering insights into AI integration and EO's complexity within the sector. The initial findings hint at the need for broader engagement strategies in the subsequent study, reflecting the challenges of researching niche markets. Significantly, the creation of the AI adoption tool marks a considerable advancement, addressing a gap in existing research tools. This study not only underscores the importance of pilot testing in social sciences, especially within specialized sectors, but also its findings and methodologies serve as a blueprint for future research, emphasizing the adaptation of strategies to industry-specific and geographical peculiarities. By establishing a methodological foundation for in-depth future research, this pilot study promises enhanced understanding of EO's impact on AI adoption strategies and performance outcomes in the Czech chemical industry, directly addressing a critical research gap.
Exploring AI Adoption Dynamics and Entrepreneurial Orientation in Czech Chemical SMEs: A Pilot Study Perspective
Keywords: Artificial Intelligence Adoption; Entrepreneurial Orientation; Czech Chemical SMEs; Pilot Study Methodology; Measurement Instrument Developmen; Artificial Intelligence Adoption; Entrepreneurial Orientation; Czech Chemical SMEs; Pilot Study Methodology; Measurement Instrument Developmen